A novel bioreactor for the generation of highly aligned 3D skeletal muscle-like constructs through orientation of fibrin via application of static strain. (15th September 2015) - Heher, Philipp; Maleiner, Babette; Prüller, Johanna; Teuschl, Andreas Herbert; Kollmitzer, Josef; Monforte, Xavier; Wolbank, Susanne; Redl, Heinz; Rünzler, Dominik; Fuchs, Christiane
Graphical abstract: Abstract: The generation of functional biomimetic skeletal muscle constructs is still one of the fundamental challenges in skeletal muscle tissue engineering. With the notion that structure strongly dictates functional capabilities, a myriad of cell types, scaffold materials and stimulation strategies have been combined. To further optimize muscle engineered constructs, we have developed a novel bioreactor system (MagneTissue) for rapid engineering of skeletal muscle-like constructs with the aim to resemble native muscle in terms of structure, gene expression profile and maturity. Myoblasts embedded in fibrin, a natural hydrogel that serves as extracellular matrix, are subjected to mechanical stimulation via magnetic force transmission. We identify static mechanical strain as a trigger for cellular alignment concomitant with the orientation of the scaffold into highly organized fibrin fibrils. This ultimately yields myotubes with a more mature phenotype in terms of sarcomeric patterning, diameter and length. On the molecular level, a faster progression of the myogenic gene expression program is evident as myogenic determination markers MyoD and Myogenin as well as the Ca 2+ dependent contractile structural marker TnnT1 are significantly upregulated when strain is applied. The major advantage of the MagneTissue bioreactor system is that the generated tension is not exclusively relying on the strain generated by the cells themselves in response to scaffold anchoring but its ability to subject the constructs to individually adjustable strain protocols. In future work, this will allow applying mechanical stimulation with different strain regimes in the maturation process of tissue engineered constructs and elucidating the role of mechanotransduction in myogenesis. Statement of Significance: Mechanical stimulation of tissue engineered skeletal muscle constructs is a promising approach to increase tissue functionality. We have developed a novel bioreactor-based 3D culture system, giving the user the possibility to apply different strain regimes like static, cyclic or ramp strain to myogenic precursor cells embedded in a fibrin scaffold. Application of static mechanical strain leads to alignment of fibrin fibrils along the axis of strain and concomitantly to highly aligned myotube formation. Additionally, the pattern of myogenic gene expression follows the temporal progression observed in vivo with a more thorough induction of the myogenic program when static strain is applied. Ultimately, the strain protocol used in this study results in a higher degree of muscle maturity demonstrated by enhanced sarcomeric patterning and increased myotube diameter and length. The introduced bioreactor system enables new possibilities in muscle tissue engineering as longer cultivation periods and different strain applications will yield tissue engineered muscle-like constructs with improved characteristics in regard to functionality and biomimicry.